FAKTOR – FAKTOR YANG MEMPENGARUHI KELENGKAPAN IMUNISASI TETANUS TOXOID PADA IBU HAMIL DI PUSKESMAS KOTA BANDA ACEH - Mariatul Kiftia (Journal of Public Health Science, 2026)
Tetanus toxoid (TT) immunization is particularly important in developing countries, especially for pregnant women, to prevent tetanus in mothers and newborns. Immunization is a process of building immunity to prevent tetanus infection. The tetanus vaccine contains an inactivated tetanus toxin. The coverage of tetanus immunization (Td+2) among pregnant women in Banda Aceh City remains low, with 1,606 pregnant women reported to have received incomplete immunization, which may contribute to increased maternal morbidity and mortality. This study employed a quantitative cross-sectional study design. The samples were selected using purposive sampling, involving 107 pregnant women from three community health centers (Puskesmas) in Aceh Province. The results showed that the majority of respondents were in the third trimester, comprising 44 respondents (41.1%). All respondents had attended antenatal care (ANC) visits, totaling 107 respondents (100%). Most respondents attended ANC according to the recommended standard of six visits, totaling 93 respondents (86.9%). The majority of respondents received education regarding TT immunization during ANC visits, totaling 99 respondents (92.5%). However, most respondents did not receive TT immunization during ANC visits, totaling 74 respondents (69.2%). All respondents had previously received TT immunization (107 respondents; 100%). Most respondents had received TT immunization only before marriage, totaling 44 respondents (41.1%). Furthermore, the majority of respondents had incomplete TT immunization status (TT1–TT4), totaling 97 respondents (90.7%). It is expected that healthcare providers will provide motivation to pregnant women and education to families regarding the importance of completing tetanus toxoid immunization to prevent infection and reduce maternal and neonatal morbidity and mortality.